2018
DOI: 10.1002/jib.523
|View full text |Cite
|
Sign up to set email alerts
|

The influence of brewing yeast strains on monoterpene alcohols and esters contributing to the citrus flavour of beer

Abstract: ‘Aroma hops’ and especially newly bred ‘flavour hops’ are used throughout the world to impart citrus‐like and/or exotic fruit‐like flavours to craft beers. Citrus‐like flavours in beer are known to be influenced by yeast fermentation when transforming certain secondary metabolites of the hops such as monoterpene alcohols. In this study, the influence of different Saccharomyces cerevisiae/pastorianus brewing yeast strains on the citrus flavour of beers hopped at different times during beer production (30 min bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In a study about wines made from hawthorn fruit juice, conducted by Zhang et al [47], it was shown that concentration of ethyl hexanoate in wines was 7 times higher than in BJ, 10 times higher than in BC, and similar to the concentration in BF. Another ester identified in hawthorn fruit and all tested beers was ethyl (4E)-4-decenoate, which is characterised by fruit (pineapple), cognac and wax flavours [48,49]. It was detected in the tested samples in the amount of 0.1267 µg/100 mL for BJ, 0.4505 µg/100 mL for BF and 0.0985 µg/100 mL for BC.…”
Section: Concentration Of Volatile Compounds In Tested Beersmentioning
confidence: 92%
“…In a study about wines made from hawthorn fruit juice, conducted by Zhang et al [47], it was shown that concentration of ethyl hexanoate in wines was 7 times higher than in BJ, 10 times higher than in BC, and similar to the concentration in BF. Another ester identified in hawthorn fruit and all tested beers was ethyl (4E)-4-decenoate, which is characterised by fruit (pineapple), cognac and wax flavours [48,49]. It was detected in the tested samples in the amount of 0.1267 µg/100 mL for BJ, 0.4505 µg/100 mL for BF and 0.0985 µg/100 mL for BC.…”
Section: Concentration Of Volatile Compounds In Tested Beersmentioning
confidence: 92%
“…Therefore, an understanding of the interaction of yeast with hop derived compounds is required. De novo synthesis of monoterpene alcohols in conventional brewer's yeast has also been reported, in both natural and genetically engineered strains (6,12).…”
Section: Introductionmentioning
confidence: 93%
“…Recently it has been reported that there can be synergistic effects on flavour formation between yeast and hops (3,4). The authors found that monoterpene alcohols from hops can be metabolised by brewer's yeast, imparting tropical and citrus flavours, however the exact mechanisms are not fully understood (3,5,6). It is not clear whether similar effects are catalysed by Brettanomyces species and an evaluation of this would aid in understanding the mechanisms behind the positive attributes of brewing with this yeast.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of key hop aroma compounds during storage at 20°C for 10 months was evaluated based on a selection of 15 hop compounds representing the major functional groups (esters, ketones, terpene alcohols, monoterpenes and sesquiterpenes) present in the essential oil. These compounds are presented in Table 4 alongside their aroma impression, and were selected because they have been identified in several studies to contribute in some form to the overall flavour of dry-hopped beers (2,6,8,9,24,25).…”
Section: Hop Aroma Profile Of Fresh Beersmentioning
confidence: 99%
“…Hops are the major source of bitterness and aroma in beer and are loosely categorised as 'bittering' , 'dual purpose' and 'aroma' varieties. Bitterness varieties are selected primarily for their bittering potential whilst 'dual purpose' hop varieties, which contain appreciable levels of both α-acids and essential oil can be applied in the brewhouse interchangeably to derive both bitterness and aroma in beer (1,2). Aroma varieties are often used to produce sensorially complex beers and are selected based on the amount and constituents of essential oil ranging from 0.5 -4% w/w of hop cones (3).…”
Section: Introductionmentioning
confidence: 99%